Disordered Books and Dynamic Archives Rabbinic Scholarly Practices in Early Modern Ashkenaz - Morsel-Eisenberg, Tamara (2021)
This article examines early modern learning through Ashkenazic responsa. Beyond explicit evidence from published responsa collections, implicit insights dwell in what these publications lack. These missing features shed light on sixteenth-century scholarly practices. The works’ organizational inconsistencies must be understood in context of learned archives. Such an adjustment offers a corrective to the regnant narrative, which views the introduction of print as a sharp rupture from earlier modes of transmission. This article suggests instead that the culture of printed books coexisted with older approaches, and that print was complemented by more disorderly and unconstrained forms of transmission. Comparing rabbinic “paper-ware” with contemporaneous humanist practices highlights the rabbi's working papers, focusing on a culture's dynamic activity rather than its stable output. This shift in perspective allows us to see rabbinic writings not merely as a collection of books but as a mode of scholarship.